2008
DOI: 10.1677/jme-08-0080
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte nuclear factor 1 binding element within the promoter of microsomal triglyceride transfer protein (MTTP) gene is crucial for MTTP basal expression and insulin responsiveness

Abstract: Insulin inhibits the transcription of the microsomal triglyceride transfer protein (MTTP), which plays a pivotal role in lipoprotein assembly and secretion. Here, we provide evidence that a hepatocyte nuclear factor 1 binding element (HNF1A element) within the MTTP promoter serves as a novel negative insulin-responsive element. Deletion/mutation mapping of the MTTP gene promoter identified a modified HNF1A element that is crucial to the negative insulin effect. Chimeric promoter containing this HNF1A element a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…We have previously shown that the consensus HNF-1 element is functionally equivalent to the slightly modified HNF-1 element found on the MTP promoter in mediating the negative insulin response [32] . This finding implies that the HNF-1-mediated negative insulin response is not only limited to the MTP gene but also to other genes containing the HNF-1 binding motif.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the consensus HNF-1 element is functionally equivalent to the slightly modified HNF-1 element found on the MTP promoter in mediating the negative insulin response [32] . This finding implies that the HNF-1-mediated negative insulin response is not only limited to the MTP gene but also to other genes containing the HNF-1 binding motif.…”
Section: Discussionmentioning
confidence: 99%